Apocalyptic claims and the everyday: Tosaka Jun, history, and journalism - Bodde, Emerson R. (Asian philosophy, 2022)
In this paper, drawing upon Tosaka Jun’s response to Interwar debates on historicism and his account of everydayness, I offer an explanation for why contemporary secular apocalyptic claims lack convergence by focusing on the historical dimension of such claims. Everydayness, organized the routines of work and rest, is shown to be the basis for a sense of historical time, and theoretical journalism is outlined as the kind of collective epistemic procedure needed to produce a collective sense of a community’s place in historical time. I defend the claim that the cause of starkly opposed responses to apocalyptic claims is due to qualitative differences in the work and rest that organize the everyday temporality. In the absence of a theoretical journalism, whether one subscribes to an apocalyptic claim will be contingent on heterogeneous personal circumstance. I conclude by outlining a limit case of indigenous post-apocalyptic claims under settler-colonialism.